Short-term effects of air pollutants on outpatients with psoriasis in a Chinese city with a subtropical monsoon climate - Wang, Ting; Xia, Yuanrui; Zhang, Xinhong; Qiao, Nini; Ke, Susu; Fang, Quan; Ye, Dongqing; Fan, Yinguang (Frontiers in Public Health, 2022)
Introduction Psoriasis is a common skin disease that seriously affects patients' quality of life. The association of air pollutants with psoriasis, and the extent of their effects remains unclear. Methods Based on a distributed lag non-linear model, this study explored the short-term effects of air pollutants on outpatients with psoriasis in Hefei, China, between 2015 and 2019 by analyzing the exposure–lag–response relationship, after controlling for confounding influences such as meteorological factors, long-term trends, day of the week, and holidays. Stratified analyses were performed for patients of different ages and genders. Results The maximum relative risks of psoriasis outpatients' exposure to SO2, NO2, and O3 were 1.023 (95% confidence intervals (CI): 1.004–1.043), 1.170 (95% CI: 1.046–1.307), and 1.059 (95% CI: 1.030–1.090), respectively. An increase of 10 μg/m3 of NO2 was associated with a 2.1% (95% CI: 0.7–3.5%) increase in outpatients with psoriasis, and a decrease of 10 μg/m3 of O3 was associated with an 0.8% (95% CI: 0.4–1.2%) increase in outpatients with psoriasis. Stratified analyses showed that male subjects were more sensitive to a change in meteorological factors, while female subjects and outpatients with psoriasis aged 0–17 years old were more sensitive to a change in air pollutants. Discussion Short-term air pollutant exposures were associated with outpatients having psoriasis, suggesting that patients and high-risk people with psoriasis should reduce their time spent outside and improve their skin protection gear when air quality is poor.